f o g ( x ) alg (g o f)

label Algebra
account_circle Unassigned
schedule 1 Day
account_balance_wallet $5

f(x)=5x and g(x)= x+6

(f o g)(x)=

(g o f)(x)=

(f o g)(3)

Jun 9th, 2015

Thank you for the opportunity to help you with your question!

f(x)=5x

g(x)=x+6

(f o g)(x)=5x*(x+6)

=5x^2+30x


(g o f)(x)=(x+6)*5x

=5x^2+30x


(f o g)(x)=5x^2+30x

when x=3

(f o g)(3)=5(3)^2+30*3

=45+90

=135



hope you happy with my answer please don't forget to rate me and leave a comment.if you have any question please let me know i'll choose the best answer for you.thank you.see you soon again...:)

Please let me know if you need any clarification. I'm always happy to answer your questions.
Jun 9th, 2015

Did you know? You can earn $20 for every friend you invite to Studypool!
Click here to
Refer a Friend
...
Jun 9th, 2015
...
Jun 9th, 2015
Sep 20th, 2017
check_circle
Mark as Final Answer
check_circle
Unmark as Final Answer
check_circle
Final Answer

Secure Information

Content will be erased after question is completed.

check_circle
Final Answer